Development of an electrochemical flow‐through cell for the fast and easy generation of isotopically labeled metabolite standards. Issue 2 (18th October 2021) - Göldner, Valentin; Fangmeyer, Jens; Karst, Uwe
Abstract: In drug development, metabolite standards of new chemical entities are required for a comprehensive safety evaluation. Stable isotope‐labeled internal metabolite standards at the milligram scale, which are difficult and expensive to synthesize in common bottom‐up approaches, are necessary for metabolite quantification using liquid chromatography/mass spectrometry. A preparative electrochemical flow‐through cell is presented here as a powerful tool for the cheap and straightforward synthesis of milligram amounts of isotopically labeled metabolite standards. The developed cell scales up established, so‐called "coulometric" electrochemical cells. Problems like electrode fouling and cross contamination between syntheses are addressed by the use of exchangeable working electrodes. The applicability of the developed cell for the synthesis of metabolite standards is demonstrated using isotopically labeled acetaminophen as a model system for the generation of a biologically relevant phase II metabolite. Abstract : Electrochemical metabolism mimicry is successfully scaled up from the analytical to the preparative scale. This allows the cheap and straightforward synthesis of stable isotope‐labeled metabolite standards at the milligram scale. These standards can then be used as calibration materials for quantification, for structural elucidation, and for toxicological evaluation of isolated metabolites.